Pembelajaran Bahasa Inggris dengan Metode Cerita, Percakapan, Latihan, dan Karya Wisata Bagi Anak Usia Sekolah Di Dusun Sambisari, Kalasan, Sleman, Yogyakarta - Rosmawati, Devi; Purwanto, Purwanto (Jurnal Pengabdian Dharma Bakti, 2020)
English in the era Industrial Revolution 4.0 became the main requirement in various sectors. Indonesia educational fields gave attention for English subject so that became a local content subject in elementary school. In providing foreign language skills to elementary school children, it needs certain methods to suit their world. Learning English for elementary school children should be suitable for their needs, such learning through play, active learning, effective learning, and fun. The aim of community service is to know the learning methods that are more preffered by the elementary school children and to provide basic knowledge on kinds of material such ‘how to introduce your self’, ‘direction’, ‘5W + 1H’. From its activities, it is found that the learning methods that is most preffered by the female elementary school children are story telling method, while games method more chosen by the male of school age children. There is an increase in knowledge of participants related to basic material ‘how to introduce your self’, ‘direction’, ‘5W + 1H’, it is proven by the results of the post test that has been done. The knowledge value of participants as many as 15 elementary school age children before learning is ± 62.80 and after the community service is ± 80.33.Keywords: Learning English, elementary school age children, learning methods